Sulfonation of IAA in Urtica eliminates its DR5 auxin activity - Supikova, Klara; Žukauskaitė, Asta; Kosinova, Andrea; Pěnčík, Aleš; De Diego, Nuria; Spíchal, Lukáš; Fellner, Martin; Skorepova, Katerina; Gruz, Jiri (Plant cell reports, 2024)
N-Sulfonated IAA was discovered as a novel auxin metabolite in Urtica where it is biosynthesized de novo utilizing inorganic sulfate. It showed no auxin activity in DR5::GUS assay, implying possible inactivation/storage mechanism. A novel auxin derivative, N-sulfoindole-3-acetic acid (IAA-N-SO3H, SIAA), was discovered in stinging nettle (Urtica dioica) among 116 sulfonated metabolites putatively identified by a semi-targeted UHPLC-QqTOF-MS analysis of 23 plant/algae/fungi species. These sulfometabolites were detected based on the presence of a neutral loss of sulfur trioxide, as indicated by the m/z difference of 79.9568 Da in the MS2 spectra. The structure of newly discovered SIAA was confirmed by synthesizing its standard and comparing retention time, m/z and MS2 spectrum with those of SIAA found in Urtica. To study its natural occurrence, 73 species in total were further analyzed by UHPLC-QqTOF-MS or targeted UHPLC-MS/MS method with a limit of detection of 244 fmol/g dry weight. However, SIAA was only detected in Urtica at a concentration of 13.906 ± 9.603 nmol/g dry weight. Its concentration was > 30 times higher than that of indole-3-acetic acid (IAA), and the SIAA/IAA ratio was further increased under different light conditions, especially in continuous blue light. In addition to SIAA, structurally similar metabolites, N-sulfoindole-3-lactic acid, 4-(sulfooxy)phenyllactic acid and 4-(sulfooxy)phenylacetic acid, were detected in Urtica for the first time. SIAA was biosynthesized from inorganic sulfate in seedlings, as confirmed by the incorporation of exogenous 34S-ammonium sulfate (1 mM and 10 mM). SIAA exhibited no auxin activity, as demonstrated by both the Arabidopsis DR5::GUS assay and the Arabidopsis phenotype analysis. Sulfonation of IAA may therefore be a mechanism for IAA deactivation and/or storage in Urtica, similar to sulfonation of the jasmonates in Arabidopsis.
Keywords: kyseliny indoloctové; Urtica dioica; regulátory růstu rostlin; Plant Growth Regulators; Phytohormone; Metabolomics; tandemová hmotnostní spektrometrie; Tandem Mass Spectrometry; Chromatography, High Pressure Liquid; Sulfonated; vysokoúčinná kapalinová chromatografie; Indoleacetic Acids; Mass spectrometry; N-Sulfoindole-3-acetic acid; Arabidopsis; Indole-3-acetic acid